Study of rare earth elements potential in acid mine drainage from coal mine: a case study. Issue 1 (May 2021) - Meriestica, F L; Badhurahman, A; Gautama, R S
Abstract: Acid Mine Drainage (AMD) is one of the crucial impacts of coal mining activities. This issue is becoming increasingly important because acid mine drainage will become a burden in the post-mining period if not appropriately managed. AMD can leach side materials, causing an increase in dissolved heavy metals, including Rare Earth Elements. REE is an essential raw material for applying modern technology whose demand is increasing globally from year to year. Until 2019, 77% of REE production came from China. The combination of scarce supply and high demand has encouraged various studies to evaluate alternative REE resources. In Indonesia, there is few research about the presence of REE in AMD from coal mine. The objective of this study to determine the amount, characteristics and enrichment mechanisms of REE in AMD, moreover this research is a preliminary study on the alternatives of REE resources. Five water samples were subjected to physical tests well as analysis of IC and ICP-MS. The water sample was 5 had a low pH of 2.90 - 3.82. The concentration of Total REE (not include Lu and Tb) from samples ranged from 0.1032 - 0.6174 ppm with an average Total REE of 0.4810 −3 ppm.